Logic, Mathematics, Philosophy, Vintage Enthusiasms Essays in Honour of John L. Bell - DeVidi, David; Hallett, Michael; Clarke, Peter; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
The volume includes twenty-five research papers presented as gifts to John L. Bell to celebrate his 60th birthday by colleagues, former students, friends and admirers. Like Bell$1 (Bs own work, the contributions cross boundaries into several inter-related fields. The contributions are new work by highly respected figures, several of whom are among the key figures in their fields. Some examples: in foundations of maths and logic (William Lawvere, Peter Aczel, Graham Priest, Giovanni Sambin); analytical philosophy (Michael Dummett, William Demopoulos), philosophy of science (Michael Redhead, Frank Arntzenius), philosophy of mathematics (Michael Hallett, John Mayberry, Daniel Isaacson) and decision theory and foundations of ecomonics (Ken Bimore). Most articles are contributions to current philosophical debates, but contributions also include some new mathematical results, important historical surveys, and a translation by Wilfrid Hodges of a key work of arabic logic.s
I History and Philosophy of Mathematics and Logic -- II Truth and Paradox -- III Logic, Set Theory and Category Theory -- IV Philosophy of Science -- V Decision Theory and Epistemology -- VI Aesthetics Index of Names Publications of J.L. Bell.
Keywords: Philosophy (General).; Genetic epistemology; Logic; Metaphysics; Science -- Philosophy; Logic, Symbolic and mathematical; Philosophy; Logic; Philosophy of Science; Epistemology; Mathematical Logic and Foundations; History of Mathematical Sciences; Metaphysics